2020
DOI: 10.1186/s12920-020-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

Six years’ experience with LipidSeq: clinical and research learnings from a hybrid, targeted sequencing panel for dyslipidemias

Abstract: Background: In 2013, our laboratory designed a targeted sequencing panel, "LipidSeq", to study the genetic determinants of dyslipidemia and metabolic disorders. Over the last 6 years, we have analyzed 3262 patient samples obtained from our own Lipid Genetics Clinic and international colleagues. Here, we highlight our findings and discuss research benefits and clinical implications of our panel. Methods: LipidSeq targets 69 genes and 185 single-nucleotide polymorphisms (SNPs) either causally related or associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 85 publications
2
37
1
7
Order By: Relevance
“…Recently, in a cohort of 563 patients with TG ≥10 mmol/L (≥885 mg/dL), we reported that 1.1% had rare biallelic variants indicating FCS (16). Furthermore, our clinical experience integrating DNA sequencing data with clinical assessments (11) confirms that FCS patients are exceedingly rare. Specifically, in our lipid clinic, we have molecularly identified a similar number of patients with FCS and homozygous FH (HoFH) (9).…”
Section: Familial Chylomicronemia Syndrome Prevalence and Clinical Fementioning
confidence: 55%
See 1 more Smart Citation
“…Recently, in a cohort of 563 patients with TG ≥10 mmol/L (≥885 mg/dL), we reported that 1.1% had rare biallelic variants indicating FCS (16). Furthermore, our clinical experience integrating DNA sequencing data with clinical assessments (11) confirms that FCS patients are exceedingly rare. Specifically, in our lipid clinic, we have molecularly identified a similar number of patients with FCS and homozygous FH (HoFH) (9).…”
Section: Familial Chylomicronemia Syndrome Prevalence and Clinical Fementioning
confidence: 55%
“…Because both common and rare variants, including SNVs and CNVs, are involved in the pathogenesis of hypertriglyceridemia, an optimal diagnostic method must be able to detect all possible variant types and bioinformatically process them en route to reporting them for potential clinical or research applications. In our experience, this is best accomplished using a targeted next-generation sequencing panel for hypertriglyceridemia, such as the LipidSeq panel (11); this panel can be used to account for different variant types disrupting the main genes involved in the TG metabolic pathway, as well as non-coding polygenic contributors.…”
Section: Analyzing Genetic Variantsmentioning
confidence: 99%
“…As diagnostic resources in many countries are limited and FH-causing variants in one of the three culprit genes are not always identified in patients with severe hypercholesterolemia, [11][12][13] the selection of FH patients who are deemed eligible for molecular testing is mostly based on clinical FH criteria such as the DLCN criteria. 14 Moreover, the yield of FH sequencing is proportionally related to the severity of the FH phenotype (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic testing 23 includes the following methods: 1) genotype only previously described DNA variants (eg, DNA microarrays or TaqMan genotyping) and/or 2) scan all DNA nucleotide positions within a single gene, a panel of selected genes, or exome of genome (see glossary), enabling detection of both previously known and newly discovered DNA variants (eg, Sanger or capillary electrophoresis sequencing, targeted next-generation gene sequencing panels, exome sequencing [ES], or genome sequencing [GS]). 23 Some targeted sequencing panels for dyslipidemia have been clinically validated 30,31 and are the current gold standard for diagnosis in dyslipidemias, 32 for example, targeted panels for FH genes, or ''pandyslipidemia'' panels for all monogenic dyslipidemias. 7,30 The same result from a targeted panel can be achieved by performing ES or GS analysis and then masking most results, reporting only findings from genes of interest.…”
Section: Key Pointsmentioning
confidence: 99%
“…23 Some targeted sequencing panels for dyslipidemia have been clinically validated 30,31 and are the current gold standard for diagnosis in dyslipidemias, 32 for example, targeted panels for FH genes, or ''pandyslipidemia'' panels for all monogenic dyslipidemias. 7,30 The same result from a targeted panel can be achieved by performing ES or GS analysis and then masking most results, reporting only findings from genes of interest.…”
Section: Key Pointsmentioning
confidence: 99%